Thermal, mechanical and moisture absorption properties of lignocellulosic waste (soda lignin)/ unsaturated polyester blends - Salinding, Diamaden T. Jr
Polymer blends from commercial orthophthalic unsaturated polyester (UP) and soda lignin obtained from alkali-treated waste sugarcane bagasse were developed. The miscibility and thermal properties of soda lignin/unsaturated polyester blend at 5, 10, 15, and 20wt% lignin content were investigated using differential scanning calorimetry, scanning electron microscopy, Fourier transform infrared spectroscopy, and thermogravimetric analysis. The presence of two glass transition temperatures and apparent phase separation revealed the immiscibility of blends which is associated with the weak intermolecular interactions as confirmed by the infra-red results. Soda lignin has slightly shifted the glass transition temperature of UP to a higher value. It also enhanced the overall thermal stability of UP over a higher temperature range, though an accelerated initial degradation of the blends was observed at lower temperatures. The tensile and flexural strength of blends were measured using universal testing machine. Increasing lignin content had insignificant effect on the tensile and flexural modulus of the polymer blend but a decrease in both tensile and flexural strength was observed. Moisture absorption of lignin/UP blends at 30ºC was characterized by weight gain measurements over time. As lignin content was increased, diffusivity decreases while absorbed moisture increases. Moisture absorption patterns were found to follow Fickian diffusion.